Mechanism of Cone Degeneration in Retinitis Pigmentosa - Song, De-Juan; Bao, Xiao-Li; Fan, Bin; Li, Guang-Yu (Cellular and molecular neurobiology, 2023)
Retinitis pigmentosa (RP) is a group of genetic disorders resulting in inherited blindness due to the degeneration of rod and cone photoreceptors. The various mechanisms underlying rod degeneration primarily rely on genetic mutations, leading to night blindness initially. Cones gradually degenerate after rods are almost eliminated, resulting in varying degrees of visual disability and blindness. The mechanism of cone degeneration remains unclear. An understanding of the mechanisms underlying cone degeneration in RP, a highly heterogeneous disease, is essential to develop novel treatments of RP. Herein, we review recent advancements in the five hypotheses of cone degeneration, including oxidative stress, trophic factors, metabolic stress, light damage, and inflammation activation. We also discuss the connection among these theories to provide a better understanding of secondary cone degeneration in RP. Graphical Abstract Five current mechanisms of cone degenerations in RP Interactions among different pathways are involved in RP.